2023
DOI: 10.1038/s41467-023-36211-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and RAD51 engagement by the BRCA2 C-terminus orchestrate DNA repair and replication fork preservation

Abstract: The tumor suppressor BRCA2 participates in DNA double-strand break repair by RAD51-dependent homologous recombination and protects stressed DNA replication forks from nucleolytic attack. We demonstrate that the C-terminal Recombinase Binding (CTRB) region of BRCA2, encoded by gene exon 27, harbors a DNA binding activity. CTRB alone stimulates the DNA strand exchange activity of RAD51 and permits the utilization of RPA-coated ssDNA by RAD51 for strand exchange. Moreover, CTRB functionally synergizes with the Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 78 publications
(166 reference statements)
5
35
0
Order By: Relevance
“…In contrast to the SA point mutation, deletion of the C terminus (∆27) causes HDR defects (Kass et al, 2016;Moynahan et al, 2001), in addition to fork protection and gap suppression defects. The ∆27 deletion includes a KKRR motif which has recently been reported to bind DNA and promote HDR as well as fork protection (Kwon et al, 2023). This motif is intact in the SA mutant.…”
Section: Brca2 Rad51-interacting Carboxyl-terminal Domain Mediates St...mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the SA point mutation, deletion of the C terminus (∆27) causes HDR defects (Kass et al, 2016;Moynahan et al, 2001), in addition to fork protection and gap suppression defects. The ∆27 deletion includes a KKRR motif which has recently been reported to bind DNA and promote HDR as well as fork protection (Kwon et al, 2023). This motif is intact in the SA mutant.…”
Section: Brca2 Rad51-interacting Carboxyl-terminal Domain Mediates St...mentioning
confidence: 99%
“…Murine BRCA2 protein is 3329 amino acids and interacts with RAD51 at the BRC repeats and at a distinct site in the C terminus that is mutated in BRCA2 S3214A (abbreviated "SA"). BRCA2 ∆27 is a truncation of 190 amino acids that deletes the C-terminal RAD51 interacting site, as well as a recently identified DNA binding motif KKRR (Kwon et al, 2023). B. HDR is not significantly affected in Brca2 SA/SA mouse cells.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Its functional relevance is now supported by the cytological (complete loss of DMC1 foci but partial retention of RAD51 foci, Figures 2-3) and biochemical (details of direct interaction between PhePP and DMC1, Figure 4) data. Our findings suggest that the FxPP consensus does not fully capture the recombinase binding requirements, as PhePP binds DMC1 and not RAD51, while the RAD51-binding “TR2” motif 38 encoded by exon 27 does not bind DMC1, despite similar core sequence (FVPP and FQPP, respectively). BRCA2 thus binds both RAD51 and DMC1 via two distinct domains: the BRC repeats, which bind monomeric forms 46 of both recombinases, and additional FxPP motifs that are recombinase-specific.…”
Section: Discussionmentioning
confidence: 84%
“…We used isothermal titration calorimetry (ITC) to determine that the small synthetic peptide F2s6, corresponding to the conserved region of F2s3, still bound to the purified untagged DMC1 with a Kd of 3.4 µM, and no interaction was observed when the same assay was performed with the F2406A mutant. In addition, testing a similar motif encoded by exon 27, in the so-called TR2 region, revealed that despite the presence of a similar (FQPP) motif, that was shown to bind RAD51 38 , this fragment does not interact with DMC1 (Figure 4E, S5D). Taken together, these results confirm the presence of a specific DMC1-interacting motif in the region encoded by exon 14 of BRCA2.…”
Section: Resultsmentioning
confidence: 99%
“…It has a stabilizing effect on RAD51-DNA complexes, counteracting BRCs 31,32 . Research on this C-terminal site was focused on S3291, which can be phosphorylated by CDKs at the G2-M transition 28,[30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%